International public administrations on Twitter: A comparison of digital authority in global climate policy - Goritz, A. (2022)
International organizations and their secretariats, called international public administrations (IPAs), have been found to hold considerable authority in world politics. This study conceptualizes and measures IPA authority in the digital sphere. It proposes the concept of digital authority to measure the authority of actors in online social networks (OSN), such as Twitter. Applying exponential random graph models (ERGMs) based on Twitter data during climate change negotiations the article compares the authority of IPAs to that of other actors. The findings show that IPAs are attributed as much authority as state actors in global climate communication networks on Twitter.